West Kalimantan’s manuscripts circulation as religious comprehensive for against violence by the name of religion - Khairul Fuad; Zulkarnain Yani; Dedy Ari Asfar; Devi Fauziyah Ma’rifat; Rohim Rohim (Cogent Arts & Humanities)
Ethnicity is deeply ingrained in the fabric of West Kalimantan, shaped by the diverse cultural backgrounds of its people, including the Malay, Dayak, and Chinese communities. The population of West Kalimantan is also characterized by various religions, such as Islam, Christianity, and Konghucu, reflecting the island’s multicultural landscape. While conflicts in the past may have been rooted in cultural differences, there is now a potential for religious-based tensions. Efforts to prevent future conflicts must urgently focus on fostering religious harmony, particularly through a comprehensive Islamic approach that discourages violence in the name of religion, a perspective gaining traction among the people of West Kalimantan. The region’s rich collection of manuscripts, with a focus on figures like Muhammad Khatib al-Sambasi, Muhammad Basuni Imran, and Ismail Mundu, can serve as valuable resources for shaping this perspective. These figures, each emphasizing Islamic doctrine, jurisprudence, and mysticism, contribute to a well-rounded understanding of religion that goes beyond one-sided claims. A scientific approach involves collecting and analyzing relevant manuscript data to advance research on countering violence in the name of religion among the people of West Kalimantan. This step is crucial for promoting a comprehensive understanding of religion and preventing the politicization of religious beliefs. Furthermore, this article aligns with government initiatives to combat terrorism by utilizing manuscripts as a tool to eliminate religious politicization and promote peace in civilization.